Contract, Conflict and Cooperation: A Critical Analysis of the Common Law Approach to the Breakdown of Modern, Complex, Symbiotic Contracts - Soper, Charles Haward (University of Leicester, 2018)
The springboard of a real-world, doctrinal, and theoretical investigation of the role played by cooperation in complex modern contracts allows me to articulate and justify a deep and concrete Transcendent Duty to Cooperate (TDTC) for these contracts. The source of the TDTC is the express words and/or the background of such contracts, the commercial expectations of the parties; which reveal that successful performance re-quires cooperation. The inevitable inference from this is that parties implicitly agree to cooperate. As the duty is implicit, it follows, I argue, that there are no gaps to be filled; merely meaning to be unearthed from the words and/or the background (construction). In doctrinal work, I review cases in categories (prevention, facilitation, defect-rectification, communication, decision-making, and active cooperation), showing that the law is far from coherent but also far from incoherent. Shifting from judicial policy making and gap-filling to context/purpose based contract construction, using evidence, is possible and would provide coherence. I create a clear and enforceable definition of cooperation through analysing the opinions of around five-hundred commercial experts and synthesising those with doctrine and theory. My empirical work analyses experts’ views; collected by interview, an online survey and workshops, using vignettes developed from adjudicated/real-life cases including opinion on what cooperation is and how it is achieved. The findings of my survey are compared with others. At an abstract level, it aligns with comparable surveys and at a detailed level, it is unique. In theoretical work, I show that basing the TDTC on construction is superior and more efficient, brings coherence to the law and that it is underpinned by shared, normative, “community” values. I test the TDTC against various “hard” cases, analysing remedial issues, showing that it would not decrease certainty in English Commercial Law, and is defensible by an appeal for coherence.

Justification for the recognition of a new nominate contract based on project defect management - Greeff, Tanya Nicole (University of Pretoria, 2018)
This research sought to establish whether the general acceptance that the common construction and engineering contracts as falling within the classification of the locatio conductio under South African law is correct. As the classification of a contract attracts specific essentialia and naturalia, and then too certain implied terms one example of an implied term that would have practical relevance is specifically investigated: The warranty against latent defects. Through this example I seek to demonstrate the relevance and importance of establishing what the classification of these contracts is, and its ensuing essentialia and naturalia. The investigation commenced by firstly considering the classification of the common building, construction and engineering contracts, with reference to the South African publications of JBCC and GCC, as well as the internationally published FIDIC Silver Book, FIDIC Yellow Book, and FIDIC Red Book, as well as the NEC ECC Option A and Option B. With alternate dispute resolution mechanisms, such as adjudication and arbitration, resulting in limited publications by way of case law and academic writing on the subject (specifically in South Africa), English law and German law were also consulted. It was established that, unfortunately, the classification of the common building, construction and engineering contracts under South African law is problematic: It does not fit the ordinary and previously accepted classifications, specifically that of the locatio conductio. This makes it questionable whether the warranty against latent defects could be, and should be, implied into any one of these contracts. The recommendation, accordingly, is that it is crucial for the construction and engineering industry to carefully consider and develop the true and relevant essentialia and naturalia applicable to these contracts. Only then will there be certainly as to what may be implied into these contracts, and what will not so be implied. Until this is achieved, the parties to these contracts, in order to have certainty, must deal with aspects such as the warranty against latent defects by way of an explicit written term in the particular contract.
Keywords: Contract; Locatio conductio

The regulatory function of contract law : comparative law and economics approach - Gramcheva, Lyubomira (European University Institute, 2015)
This thesis challenges the traditional view of national contract laws as facilitative regimes and argues that contract law on the national level has been progressively re-oriented to perform an efficiency-driven regulatory function. To develop the argument the thesis studies the contract law remedial regime of two common law and one civil law jurisdiction – the US, England and Bulgaria, in two specific contracts – the sale-of-goods and the construction contract. The introductory chapter puts the main theme in context and outlines the project. Exploring the limits of promissory theory and neoclassical economics, the second chapter develops an innovative interdisciplinary methodology joining the new institutional economics with the comparative law method. The third, fourth and fifth chapters offer taxonomies of remedies, types of contracts and remedial effects to set the stage for a meaningful comparison across the different legal traditions. Since economic theory has advanced most in the study of incentives generated by damages, the third chapter focuses on the latter remedy and shows that the common law classification of damage measures (expectation, reliance, restitution), on which traditional law-and-economics accounts are based, can be applied to study a civil law jurisdiction like Bulgaria. Distinguishing discrete and long-term contracts and demonstrating that the differentiation between sale-of-goods and construction contracts in the compared national legal systems does not necessarily go along the lines of the discrete/long-term distinction in economics, the fourth chapter argues that the positive comparison should be made with an eye on the market for substitute performances even if the compared factual scenarios are classified under different legal categories in the different jurisdictions. For the uninitiated, the fifth chapter reconstructs and criticises the standard economic model rationalising damages as incentives. The final chapter applies the approach developed here to contractual termination. The exemplary analysis identifies trends in the compared legal systems and suggests that all of them converge in charging the termination remedy with a regulatory function. Finally, I generalise to make some bolder claims about contract law.
Keywords: Contracts; Law and economics; Public law (Economic aspects)